Explosion Box Media Based on Science Literacy to Improve Elementary School Science Learning Outcomes - Dewa Ayu Prilya Astari Dewa; I Made Citra Wibawa; I Kadek Suartama (Universitas Pendidikan Ganesha, 2025)
The science literacy ability of grade V elementary school students is still low, especially in understanding the concept of science fiction. This is exacerbated by the lack of use of learning media that is contextual, interesting, and in accordance with student characteristics, resulting in low student learning outcomes. This research aims to produce Explosion Box learning media based on science literacy on harmony materials in the ecosystem to improve the learning outcomes of IPAS students in grade V of elementary school, which has been tested in terms of validity, practicality, and effectiveness. The research was conducted using the ADDIE model. The data collection method uses interview, questionnaire and test methods and the data analysis techniques used are qualitative and quantitative analysis. The results of this study are in the form of (1) producing the design of the Explosion Box media, (2) testing the validity of the Explosion Box media, finding the average validity by material experts and media experts with valid/feasible qualifications, (3) testing the practicality of the Explosion Box media found by teachers with very good qualifications while by students with very good qualifications, (4) and testing the effectiveness of media use Explosion Box uses a one group pre-test post-test design to get correlated t-test results with the results of Explosion Box media effectively used to improve student learning outcomes. Based on these results, it was concluded that science literacy-based Explosion Box media is a valid, practical, and effective learning media to improve the learning outcomes of science science students in grade V of elementary school.